„Był wieśniakiem, miał żonę i dzieci, ale nie był przez to gorszy w sprawach Bożych ” – instytucja małżeństwa w "Historii kościelnej" Sozomena z Bethelii - Bralewski, Sławomir (Vox Patrum, 2026)
Sozomen of Bethelia, the author of the Ecclesiastical History, included in his work a number of reflections on various secondary topics related to the course of the lives of the heroes of his narrative. One of them was undoubtedly the institution of marriage. In this article, starting from Sozomen's observations about Spyridon, Bishop of Trimithus in Cyprus, I have attempted to reconstruct the general picture of this institution as it functioned in the Christian environment of Sozomen's times. To this end, I have analyzed the historian's loose thoughts on marriage scattered throughout the work. In doing so, I have also tried to establish his views on marriage.